TEACHING THE RUSSIAN LANGUAGE USING THE TECHNOLOGY OF ENLARGED DIDACTIC UNITS IN PRIMARY GRADES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The main goal that determines the direction of the entire process of teaching the Russian language in primary grades is the development of oral and written speech of primary schoolchildren. The whole history of Russian progressive pedagogical thought and the history of culture requires that a child studying at school master the norms of the national literary language. Without mastering the native language, further education and general development of the student is impossible.